To Cheat or Not To Cheat: Moral Hazard and Agri‐environmental Policy. (19th August 2013) - Fraser, Rob
Abstract This Address examines the moral hazard problem in agri‐environmental policy. It begins with a theoretical analysis of moral hazard in this context, including the identification of eight potential causes of cheating behaviour among farmers. But is cheating behaviour among farmers actually a problem for agri‐environmental policy? And if it is, which are the statistically significant causes of concern? The answer seems to be: "we don't know" as there are currently no empirical analyses of the moral hazard problem and its causes in agri‐environmental policy. On this basis I analyse a set of policy solutions – to a problem for which we have no evidence of its causes or extent!